Producing For A Short Film: Short Film Abroad as A Study Case - Bernadus Yoseph Setyo Prabowo (Universitas Multimedia Nusantara, 2017)
ABROAD is a short film, which tells a story of an Indonesian student, Priyo (23) who lived in Brisbane. He had to live in his yellow car, after finding out that his scholarship had been corrupted. Priyo began his new journey when he met Pamela (17), a runaway musician who was stuck in Brisbane for a night during her trip to Sydney. Their friendship grows stronger when they played music and performed together at Brisbane streets. Unfortunately, Priyo’s car was vandalized due to his religion. Later on, their friendship was tested as they explore the city for the first time. The film explores the journey to find the meanings of passion, dream, and faith. Depicted by the main character who is an Indonesian student, the film attempts to share the experience of students who chose to travel outside their home country, in search of better education for better life. Although most part of the story is fiction, the main character (Priyo) is inspired by the real life experience of an Indonesia student in Canberra. He lived in his car for two year while trying to complete his master degree. Dramas that were presented in the storyline were based on the writer’s observation toward his surroundings, friends, and communities. Living and studying in another country could bring great experiences to international students, but at the same time, living through differences in values and beliefs could be a challenging task. The meaning of ‘abroad’ is not just about people who live outside their home country. But, it could also depict people’s experience when they try to get out of their comfort zone in order to achieve a higher goal in their life. Based on these reasons, the main targeted audiences of the film are people from the age of 25 and above. Additionally, the film also attempts to target local audiences, especially parents, as a bridge between parents and children. Hopefully it could prevent the rising number of runaway’s children. The outline of the production begins with the script development, which will be completed by the end of November. As soon as the final script is done, the production will proceed with the pre-production from December until early January. This process includes assembling the crew, finding cast, art design, and composing music. The crew will consist of GFS students for the production crew and some Indonesian students who voluntarily want to help in funding and marketing. The production will start around late January or early February, Bernadus Yoseph Setyo Prabowo adalah staf pengajar pada Program Studi Televisi dan Film, Universitas Multimedia Nusantara. e-mail: bernadus.yoseph@umn.ac.id 54 Vol. X, No. 2 Desember 2017 and the post-production will begin in March. There are some challenges in this project. Firstly, the project has to combine two different cultures between Indonesia and Australia through out the process. However, having an Australian as the director and an Indonesian as the producer can solve these. The other problem is related to the sensitive issue around religion, especially Islam. Recently, the religion feels being judged in Australia because of the action of ISIS (Islamic State in Iraq and Syria) and ISIL (Islamic State in Iraq and Levant). There will be three problems that are going to be discussed in order to resolve the challenges of the project. Keywords: short film, film production, Abroad